Pengaruh Terpaan Tayangan BTS â€œBON Voyage (Season 4)â€ Terhadap Minat Traveling Komunitas BTS Army Indonesia Ke New Zealand - Aqilah Julieta Firdausi; Guntur F. Prisanto (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
The purpose of this study was to determine the effect of BTS "Bon Voyage (Season 4)" exposure on the Indonesian BTS ARMY Community interest in traveling to New Zealand. This research uses Quantitative Research Methods and uses Media Exposure Theory. The results of the regression test obtained through the coefficient of determination test (R Square) yielded a value of 0.232 or 23.2%. This value shows that only 23.2% of Y variable (BTS ARMY Indonesian Community Interest in Traveling to New Zealand) can be explained or predicted by X variable (Influence of BTS "Bon Voyage (Season 4)"). Then from the results of hypothesis T test between X and Y variables showed a significance value of 0.000 which means sig (p) <0.05, so Ha is accepted and Ho is rejected. The conclusion, there is a weak influence between watching the BTS "Bon Voyage (Season 4)" on BTS ARMY Indonesian Community Interest in Traveling to New Zealand. In addition, the simple regression model formed is: Y = 7883 + 0.144 X. It can also show that every 1 unit increase in variable (X) will cause an increase in variable (Y) of 0.144.